New techniques for brand management in the healthcare sector - Borges, Ana Pinto, 1980- (Advances in marketing, customer relationship management, and e-services (AMCRMES) book series., 2021)
"This book explores the diffusion of new marketing knowledge, tendencies, and qualitative and quantitative methods for brand management in the private, public, and social health sectors and examines the movement from healthcare as a priceless commodity to one that can be, and is, commodified"--